Implementasi CMS Wordpress dalam Meningkatkan Promosi MAS Terpadu Guguak Randah - Ferza, Zilma; Annas, Firdaus; Jasmienti, Jasmienti; Yuspita, Yulifda Elin (Intellect : Indonesian Journal of Learning and Technological Innovation, 2023)
This article aims to produce a system plan in the form of a school website using WordPress CMS in promotional efforts at Guguak Randah Integrated MAS. This is because the school still uses conventional promotional media to convey information to the public, which has resulted in this madrasah not yet becoming well-known and its existence known. The impact is that there are no new student applicants available each school year because the information obtained is very limited. The research uses the development method or Research and Development (R&D) with the RAD (Rapid Application Development) development model which consists of three stages, namely the Requirement Planning, Design Workshop, Implementation stages. The findings of this research are in the form of a responsive website design that presents information about madrasas that is valid, practical and effective. From the product validity test results, a value of 0.76 was obtained in the very valid category, practicality test results from 3 respondents obtained a value of 0.91 in the very high category, and effectiveness test results from 9 assessors obtained a value of 95.11 in the very effective category. Abstrak Artikel ini bertujuan untuk menghasilkan sebuah rancangan sistem dalam bentuk website Sekolah Menggunakan CMS WordPress dalam Upaya Promosi di MAS Terpadu Guguak Randah. Hal ini disebabkan bahwa sekolah masih menggunakan media promosi konvesional dalam menyampaikan informasi kepada masyarakat yang mengakibatkan madrasah ini tidak belum begita terkenal dan diketahui keberadaannya. Dampaknya adalahnya kurangnya penimat siswa baru disetiap tahun ajaran disebabkan informasi yang didapatkan sangat terbatas. Penelitian menggunakan metode pengembangan atau Research and Development (R&D) dengan model pengembangan RAD (Rapid Application Development) yang terdiri dari pada tiga tahapan yaitu tahapan Requirements Planning, Design Workshop, Implementations. Temuan penelitian ini berupa rancangan website yang responsive dengan menyajikan informasi seputar madrasal yang valid, praktis dan efektif. Dari hasil uji validitas produk didapatkan nilai 0,76 dengan kategori sangat valid, hasil uji praktikalitas dari 3 orang responden diperoleh nilai 0,91 dengan kategori sangat tinggi, dan hasil uji efektivitas dari 9 orang penilai diperoleh nilai 95,11 dengan kategori sangat efektif.